LATIHAN KESEIMBANGAN DENGAN METODE LEE SILVERMAN VOICE TREATMENT (LSVT) BIG PADA LANSIA - Febri Arifiati, Retna; Sriwahyuni, Endang (Jurnal Indonesia Mengabdi, 2024)
Based on the period of life, someone entering old age will experience many setbacks. This setback will be faced with various kinds of health problems. These health problems occur because elderly people experience various kinds of functional changes resulting from a decrease in physiological and psychological functions which have an impact on changes in sensory function, neurological, cognitive and musculoskeletal systems. With the neurological changes and musculoskeletal changes that occur in the elderly, this will result in an inability to control balance, resulting in slow movements, increasing the risk of falls, which ultimately disrupts daily activities. This community service activity was carried out through a group approach at the elderly posyandu in Tempuran Village, Bolon, Colomadu Karanganyar using the balance training method with the LSVT BIG method starting from pretest, intervention, posttest. Based on hypothesis testing using the Paired Sample T-Test, a significance value of 0.000 (p<0.005) was obtained, which means that LCVY BIG balance training has an effect on improving the balance of elderly people in carrying out daily activities.